Digital Heritage Interpretation for Sustainable Tourism in the Subak Cultural Landscape of Bali - Dinar Sukma Pramesti; Dwi Novita Cahyaningtyas Permatasari; Ong Chuan Huat (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Tourism experiences in heritage landscapes are frequently dominated by visual appreciation, resulting in limited understanding of the cultural philosophies embedded within traditional management systems. Jatiluwih Village in Bali, internationally recognized for its terraced rice fields and the Subak irrigation system as a UNESCO World Cultural Heritage Site, faces similar challenges, where visitor engagement remains largely superficial. This study aims to develop and evaluate a digital-based heritage interpretation strategy that enhances cultural understanding and supports sustainable tourism. Using a Research and Development approach adapted from the Borg and Gall model, the study comprised preliminary research, prototype development, and limited field trials. Data were collected through surveys of one hundred and fifty tourists, semi-structured interviews, and focus group discussions with pekaseh, tour guides, and village tourism managers. Quantitative data were analyzed descriptively, while qualitative data were examined using thematic analysis. The results indicate that more than seventy per cent of visitors had limited prior knowledge of Subak, despite demonstrating a strong interest in digitally mediated learning. Interactive digital books integrated with Quick Response codes emerged as the most preferred interpretation medium, followed by educational videos, with the majority of respondents willing to access heritage information digitally on-site. Limited trials further demonstrate that the digital interpretation prototype enhanced visitor engagement, strengthened tour guides’ interpretive capacity, and reduced narrative inconsistencies. This study contributes to heritage tourism literature by illustrating how digital interpretation can function as an effective edutourism mechanism, facilitating cultural transmission and reinforcing sustainable heritage management through collaborative stakeholder involvement.